2009
DOI: 10.1091/mbc.e09-07-0643
|View full text |Cite
|
Sign up to set email alerts
|

The M Phase Kinase Greatwall (Gwl) Promotes Inactivation of PP2A/B55δ, a Phosphatase Directed Against CDK Phosphosites

Abstract: We have previously shown that Greatwall kinase (Gwl) is required for M phase entry and maintenance in Xenopus egg extracts. Here, we demonstrate that Gwl plays a crucial role in a novel biochemical pathway that inactivates, specifically during M phase, "antimitotic" phosphatases directed against phosphorylations catalyzed by cyclin-dependent kinases (CDKs). A major component of this phosphatase activity is heterotrimeric PP2A containing the B55delta regulatory subunit. Gwl is activated during M phase by Cdk1/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
202
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(224 citation statements)
references
References 37 publications
(87 reference statements)
17
202
0
5
Order By: Relevance
“…It is capable of reversing the effects of CDK-mediated positive regulation through dephosphorylating Cdc25 and Wee1 (refs 32,33). In addition, PP2A is particularly important for timely dephosphorylation of various CDK substrates during mitotic exit 34 . PP2A, thus, opposes not only CDK activation but also its activity by dephosphorylating downstream effectors to promote efficient cell cycle progression.…”
mentioning
confidence: 99%
“…It is capable of reversing the effects of CDK-mediated positive regulation through dephosphorylating Cdc25 and Wee1 (refs 32,33). In addition, PP2A is particularly important for timely dephosphorylation of various CDK substrates during mitotic exit 34 . PP2A, thus, opposes not only CDK activation but also its activity by dephosphorylating downstream effectors to promote efficient cell cycle progression.…”
mentioning
confidence: 99%
“…Similarly, inactivation of the cyclin B-Cdc2 complex by cyclin B degradation was sufficient to trigger mitotic exit. However, recent data from our and other laboratories has demonstrated that PP2A is highly regulated during mitotic entry and exit (3,10,11). Therefore, the old cell-cycle model now must be updated to include a different regulator of mitosis that modulates PP2A during this phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that depletion of Gwl in Xenopus egg extracts both prevents mitotic entry and promotes mitotic exit (8,10,11).…”
Section: Mast-l Is the Functional Human Homolog Of Xenopus Greatwallmentioning
confidence: 99%
See 2 more Smart Citations